The Effect of Block Play on Fine Motor Development Among Children in Pre-School - Fauziah, Resti; Puspitasari, Amalia Indah (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: to find out the influence of block games on the development of fine motor skills in preschool children aged 4-5 years at TKAT ARRIDLO. Methods: this study used an experimental type of research with a pre- experimental design using a pre-test and post-test design. The population in this study were all preschool children at TKAT ARRIDLO who experienced fine motor development disorders. The sampling technique is to use the entire total population so that the total sample is 17 people. The results of the study were then analyzed using the Wilcoxon test. Results: The research revealed that 11.8% of children had untested fine motor development before a block game, while 82.2% had suspect development. After the game, 29.4% had suspect development, and 70.6% had normal development. The Wilcoxon test indicated H1 as accepted. Conclusions: this shows that there is an effect of playing with blocks on the fine motor development of preschoolers at TKAT ARRIDLO. It is hoped that research sites can routinely apply games that train children's motor development, especially fine motor skills.